ترجمة الأفعال المركبة الإنجليزية إلى العربية عبر الترجمة الآلية "جوجل" (Google Translate) - Nursyahzirah Ismail
Phrasal verbs are known as compositional verbs that consist of lexical verbs with particles or preposition. The translation of phrasal verbs in other languages can be difficult because the semantics of phrasal verbs cannot be addressed by analysing them separately. This research aims to find out the accuracy of translating English phrasal verbs into Arabic language using Google Translate. By adopting stratified random sampling method, this research focuses on 100 English phrasal verbs from Cambridge Grammar Book “English Phrasal Verbs in Use”. This research uses a qualitative approach based on document analysis method in collecting data. The results of this study show that translating phrasal verb via Google Translate do not always suit its real meaning and context of the sentences in target language. Thus, translators must check and improve the translation proposed by Google Translate before accepting it.